The dignity of the sick in terminal situation - Campos Olazabal, Patricia (2020)
The dignity of the terminally ill patient must be appreciated, for the condition of being human, showing the corresponding dignity for the fact of "being", of the existence. It is known that terminal situations change the conditions in which the patient finds himself, but it is not lawful to claim that circumstances affect his intrinsic dignity, in the same way that it cannot be claimed that because he is in a terminal situation he does not have the right to lifetime. Adverse circumstances may be present in the life of the human being, but it will always be an end and never a means, within which the dignity of the terminally ill patient must be respected, and the necessary conditions must be ensured of how the corresponding care will be provided until the end. of your life, but not direct actions aimed at when to end your life.